(untitled) (Balneo and PRM Research Journal, 2024)
Neurofilaments are crucial in neuronal cytoskeleton formation, influencing axonal growth and impulse modulation. This study focuses on understanding the dynamics of the phosphorylated neurofilament heavy subunit (pNFH) in pediatric spinal muscular atrophy (SMA) patients undergoing Nusinersen treatment. The presence of five neurofilament types, particularly pNFH, is explored as a potential biomarker. SMA, an autosomal recessive disease impacting motor neurons, is characterized by disease severity linked to the number of SMN2 gene copies. Approved drugs, including Nusinersen, have demonstrated efficacy in enhancing motor activity. Methods: A retrospective analysis was conducted on 18 pediatric SMA patients treated with Nusinersen from October 2018 to July 2023. Cerebrospinal fluid (CSF) samples were utilized to assess pNFH levels. Motor scales were employed to evaluate performance, focusing on patients with varying SMN2 gene copies. Results: Following the initiation of Nusinersen treatment, a substantial decrease in pNFH levels was observed in CSF samples. Motor scales indicated improved performance, particularly in patients with more SMN2 copies. However, the correlation between pNFH levels and motor improvement was not strongly evident, suggesting a limited role as a prognostic indicator within this timeframe. Conclusion: Nusinersen effectively reduced pNFH levels in pediatric SMA patients, showcasing promising outcomes in motor function. However, the predictive value of pNFH remains inconclusive, emphasizing the need for further research. Study limitations, including the rarity of SMA, the absence of a control group, and the disease’s dynamic nature over time, should be considered when interpreting these findings.